Samband mellan galtars sociala beteende, ätbeteende och resultat i stationsprövning - Andersson, Annelie (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2006)
A study on the behavioural patterns of growing boars is presented. The study was preformed at Quality Genetics' boar testing station Månseryd in Sweden. The boars were purebred Yorkshire, Hampshire or Landrace, born in nine different nucleus farms. The study is based on two batches of boars, with 63 and 69 boars respectively.